Access to Behavioral Health Care for Geographically Remote Service Members and Dependents in the U.S. - Brown, Ryan Andrew (RAND Corporation, 2014)
Concerns about access to behavioral health care for military service members and their dependents living in geographically remote locations prompted research into how many in this population are remote and the effects of this distance on their use of behavioral health care. The authors conducted geospatial and longitudinal analyses to answer these questions and reviewed current policies and programs to determine barriers and possible solutions.